If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + 6z) = 0 (3 * 3 + 6z * 3) = 0 (9 + 18z) = 0 Solving 9 + 18z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 18z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 18z = 0 + -9 18z = 0 + -9 Combine like terms: 0 + -9 = -9 18z = -9 Divide each side by '18'. z = -0.5 Simplifying z = -0.5
| 3y-21=12 | | (1+9c)(6)= | | 55+54+54+x+74=180 | | F(2x+1)=6x | | 132+8x=180 | | 2x+3=27+x | | 4y+1=y^2 | | b/5=40 | | (1+5p)(4)= | | 5x-19=x+14 | | 30x^2-54x=0 | | =(5x^2-4x+5)(4-x^2) | | 180=110[7x] | | y=2(x+4)2-3 | | X-25=-48 | | 20y-5= | | 6w=w^2 | | 2x+11=6x-1 | | 4(2b+1)=13+2b | | 10p+4= | | 4(2h+1)=13+2b | | 2(x+5)=y+6 | | 7(1+3n)= | | 10x-5=5x-25 | | 1.5(x-3.1)=11.25 | | q-12=1+12 | | -19/2-33/2=7 | | (2+4q)(4)= | | ln8/9x^9y | | 19/2-33/2=7 | | y=12x^2+14x+4 | | 2x-3+x+3= |